2023
DOI: 10.3390/cancers15030570
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery after Surgery (ERAS) Program for Patients with Peritoneal Surface Malignancies Undergoing Cytoreductive Surgery with or without HIPEC: A Systematic Review and a Meta-Analysis

Abstract: Enhanced recovery after surgery (ERAS) program refers to a multimodal intervention to reduce the length of stay and postoperative complications; it has been effective in different kinds of major surgery including colorectal, gynaecologic and gastric cancer surgery. Its impact in terms of safety and efficacy in the treatment of peritoneal surface malignancies is still unclear. A systematic review and a meta-analysis were conducted to evaluate the effect of ERAS after cytoreductive surgery with or without HIPEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Recently, many studies reported the effectiveness of ERAS across surgical procedures mainly evaluated by doctor-reported outcomes and length of hospital stay 2–4. However, new information is necessary for better uncovering the value of ERAS on patients receiving surgeries, such as the advance of anaesthetic drugs and the availability of implemented tool to assess patient-reported outcomes, as the ERAS Society guideline recommended 5 6. A variety of patient-reported outcomes, such as postoperative quality of recovery (QoR) or the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36), have currently been used to measure the impact of ERAS, alongside conventional doctor-reported outcomes and length of hospital stay 7–9…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies reported the effectiveness of ERAS across surgical procedures mainly evaluated by doctor-reported outcomes and length of hospital stay 2–4. However, new information is necessary for better uncovering the value of ERAS on patients receiving surgeries, such as the advance of anaesthetic drugs and the availability of implemented tool to assess patient-reported outcomes, as the ERAS Society guideline recommended 5 6. A variety of patient-reported outcomes, such as postoperative quality of recovery (QoR) or the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36), have currently been used to measure the impact of ERAS, alongside conventional doctor-reported outcomes and length of hospital stay 7–9…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, Kehlet H et al discovered of ERAS (Kehlet and Wilmore 2008). The key elements of ERAS program include patient and family education and counseling, patient optimization prior to admission, minimal fasting (light meal up to six hours before surgery, carbohydrate beverage two hours before anesthesia), multimodal analgesia with appropriate use of opioids, nausea and vomiting prophylaxis, early nutrition and mobilization (Robella et al 2023). Hospital stays and immobilization, as risk factors for VTE, are reduced by ERAS (Cho et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing level of experience with ERAS principles in colorectal surgery, it seemed the appropriate time to apply the ERAS principles to advanced rectal cancer surgery. In several high-expertise fields, such as upper gastro-intestinal surgery and cytoreductive surgery with hyperthermal intraperitoneal chemotherapy, ERAS implementation has seemed promising, with good postoperative results [7,[11][12][13]. Therefore, a tailored ERAS protocol for locally advanced and recurrent rectal cancer (LARRC) has been developed by a multidisciplinary team with expertise in advanced rectal cancer [10].…”
Section: Introductionmentioning
confidence: 99%